REKONSTRUKSI NALAR KEBERAGAMAAN; TEKSTUR BARU DIALEKTIKA PEMAKNAAN TEKS DAN KONTEKS - Hijrian A. Prihantoro (Institut Agama Islam Ngawi, 2016)
The event of Islamic studies contest strives to inculcate sensitivity towards the diversity of meaning to religious texts. The journey of religious logical reasoning is one form of proof that the world of Islamic scientific can change the perspective and mindset of a civilization. The history of Islamic legal reasoning formulations during the mujtahidin in the disciplines of usul fiqh (Islamic legal theory) have shown us how the law is growing and not stagnant. Observations in monitoring natural phenomena, cultural and social facts are constantly changing and evolving so great, be one factor that certainty understanding or a new way to read religious texts. Therefore, if the literature of jurisprudence affirmed how a law can be changed when objective criteria (al-'illah) change, then the sociology of knowledge can be stated also that social change produces a change of understanding.